1997
DOI: 10.1080/01448765.1997.9755187
|View full text |Cite
|
Sign up to set email alerts
|

Spiders of the Foliage and Herbaceous Layer of an IPM Apple Orchard in Kecskemét-Szarkás, Hungary

Abstract: As part of a broad agroecological project, spiders were collected in different blocks of a 6 ha experimental !PM apple orchard at Kecskemet-Szarkas, Hungary, in 1994. The orchard was divided into six blocks receiving different treatments: the two "traditional" blocks were treated with conventional intensive spraying; the two "!PM" blocks were managed under an integrated pest management scheme. In the "IPM+flowers" blocks the same !PM scheme was applied and, additionally, flowering herbs were sown between tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…The major factors responsible for this are a direct effect of broad-spectrum insecticides and the lack of prey after the treatments. Other authors found that the abundance of spider communities did not differ significantly between IPM systems based on selective insecticides (diflubenzuron, fenoxycarb) and conventional management systems based on broad-spectrum insecticides (Olszak et al, 1992a;Samu et al, 1997). Olszak et al (1992a) considered that their results could be strongly influenced by prey density.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The major factors responsible for this are a direct effect of broad-spectrum insecticides and the lack of prey after the treatments. Other authors found that the abundance of spider communities did not differ significantly between IPM systems based on selective insecticides (diflubenzuron, fenoxycarb) and conventional management systems based on broad-spectrum insecticides (Olszak et al, 1992a;Samu et al, 1997). Olszak et al (1992a) considered that their results could be strongly influenced by prey density.…”
Section: Discussionmentioning
confidence: 93%
“…In the strips, where the herbaceous layer was manipulated, higher spider communities developed in the canopy, which was probably caused by the availability of suitable overwintering places for spiders and the higher prey density composed of indifferent insects coming from the herbaceous layer. Samu et al (1997) stated, however, that the relationship between canopy and herbaceous layer is limited because they have different spider family compositions and there is little evidence that adding herbs to the herbaceous layer would increase the abundance of spiders in the canopy.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some spiders will move vertically and search the crop plant. Even in apple orchards, some species found on the ground cover vegetation, below and between trees, were also found on the trees themselves (Samu et al, 1997;Yu-hua et al, 1997). Altieri & Schmidt (1986b), however, reported that high numbers of predators on cover crops did not always translate into higher numbers on the apple trees, and they advocated investigating whether mowing the cover crop would stimulate predators to ascend into the tree foliage.…”
Section: Mechanisms Of Spider Action In Diversified Habitatsmentioning
confidence: 99%
“…Esta subamostragem também é um reflexo da grande porcentagem de indivíduos imaturos (não passíveis de identificação específica) coletados através do GCE e das AQ, correspondendo a mais de 80% do total de indivíduos examinados, como também encontrado por Brierton et al (2003) e Samu et al (1997). Este fato é amenizado em famílias como Araneidae e Thomisidae, em que alguns táxons possuem características morfológicas distintivas permitindo seu reconhecimento em nível específico (Jiménez-Valverde & Lobo 2006).…”
Section: Resultsunclassified